A Growing Smile and a growing demise: the diminishing value of Damietta furniture making - Hamoud, Maher; Diab, Osama (My University, 2022)
Using the Growing Smile framework, we argue in this article that the struggles of manufacturers in the Egyptian furniture industry is part of a historical and structural process characterized by a drop in value added by the manufacturing processes, giving way to higher value added by the pre- and post-manufacturing processes. We found that manufacturers surviving this trend are the ones who can integrate advanced design and marketing techniques in their processes, and in some cases outsource the manufacturing process altogether, while focusing instead on design and marketing. These are large players who increasingly operate and employ workers from Egypt's large metropolises, namely Cairo. This causes the redistribution of value to Cairo-based business and professions at the expense of the provincial city of Damietta. Internationally, with increased automation, more of the value is captured by the manufacturers of IP-heavy machines at the expense of traditional craftsmen. These trends have serious repercussions on an increasingly industrialising Global South, prominently among which is a rapidly falling employment-to-population ratio.
Keywords: Automation; Damietta; furniture; growing smile; value chains